2014
DOI: 10.14348/molcells.2014.0153
|View full text |Cite
|
Sign up to set email alerts
|

A Medium-Chain Fatty Acid, Capric Acid, Inhibits RANKL-Induced Osteoclast Differentiation via the Suppression of NF-κB Signaling and Blocks Cytoskeletal Organization and Survival in Mature Osteoclasts

Abstract: Fatty acids, important components of a normal diet, have been reported to play a role in bone metabolism. Osteoclasts are bone-resorbing cells that are responsible for many bone-destructive diseases such as osteoporosis. In this study, we investigated the impact of a medium-chain fatty acid, capric acid, on the osteoclast differentiation, function, and survival induced by receptor activator of NF-κB ligand (RANKL) and macrophage colony-stimulating factor (MCSF). Capric acid inhibited RANKL-mediated osteoclasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Correlations between anthropometric and biochemical parameters in men and women with CKD showed various relations resulting from the duration of the treatment of both groups of patients (46.29 and 62.46 months, respectively). The observed relations involve capric acid (C10:0) and are connected to the fact that this acid inhibits receptor activator for nuclear factor κ B ligand (RANKL NF-κB)-dependent osteoclastogenesis, as the level of capric acid decreases together with a longer period of treatment [33]. Albuminuria is a strong, independent prognostic factor for chronic kidney disease, and ferritin in blood plasma, formed due to cell damage, is a well-known marker of inflammation; thus, the correlations are observable [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between anthropometric and biochemical parameters in men and women with CKD showed various relations resulting from the duration of the treatment of both groups of patients (46.29 and 62.46 months, respectively). The observed relations involve capric acid (C10:0) and are connected to the fact that this acid inhibits receptor activator for nuclear factor κ B ligand (RANKL NF-κB)-dependent osteoclastogenesis, as the level of capric acid decreases together with a longer period of treatment [33]. Albuminuria is a strong, independent prognostic factor for chronic kidney disease, and ferritin in blood plasma, formed due to cell damage, is a well-known marker of inflammation; thus, the correlations are observable [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the studies regarding saturated fat rich in MCFA are focused on its metabolic effects such as reduced body fat mass and enhanced insulin sensitivity (Schönfeld & Wojtczak, ; St‐Onge et al, ; Wein et al, ). Only few studies have investigated MCFA role on bone mass and bone remodeling (Doucette et al, ; Kim, Yoon, Kim, & Yoon, ; Nonaka et al, ). There has only been one short‐term that study has evaluated the effect of HFD rich in MCFA on non‐diabetic mouse bone, and it was unchanged after 2 weeks of dietary intervention (Doucette et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kim et al suggested that a medium-chain fatty acid suppressed osteoclastogenesis by inhibiting RANKL-induced IκBα phosphorylation, p65 nuclear translocation, and NF-κB transcriptional activity. They also found that NFATc1 was inhibited by medium-chain fatty acid in osteoclastogenesis in conventional culture system [ 31 ]. In contrast, we found that fatty acid biosynthesis, mainly of saturated fatty acid, was upregulated in mitochondrion of osteoclasts formed in the low serum culture system.…”
Section: Discussionmentioning
confidence: 99%